2007
DOI: 10.1038/nature06231
|View full text |Cite
|
Sign up to set email alerts
|

Probing the chemistry of thioredoxin catalysis with force

Abstract: Thioredoxins are enzymes that catalyse disulphide bond reduction in all living organisms 1 . Although catalysis is thought to proceed through a substitution nucleophilic bimolecular (S N 2) reaction 1,2 , the role of the enzyme in modulating this chemical reaction is unknown. Here, using single-molecule force-clamp spectroscopy 3,4 , we investigate the catalytic mechanism of Escherichia coli thioredoxin (Trx). We applied mechanical force in the range of 25-600 pN to a disulphide bond substrate and monitored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
315
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(325 citation statements)
references
References 44 publications
7
315
0
3
Order By: Relevance
“…25,26 Most likely, this interface is generally used for specificity in interaction, and possibly also to generate correct alignment of target disulfide bonds with Cys 32, which single-molecule studies suggest requires rearrangement at the interface for formation of the intermolecular disulfide bond intermediate. 27,28 …”
Section: Functional Protein-protein Interfacementioning
confidence: 99%
“…25,26 Most likely, this interface is generally used for specificity in interaction, and possibly also to generate correct alignment of target disulfide bonds with Cys 32, which single-molecule studies suggest requires rearrangement at the interface for formation of the intermolecular disulfide bond intermediate. 27,28 …”
Section: Functional Protein-protein Interfacementioning
confidence: 99%
“…This enhancement is also evident in the lag-time values, which are significantly reduced in the case of V3 ( Figure 4C). Recent single-molecule force-clamp spectroscopy studies [37] have revealed two alternative forms of the catalytic mechanism of E. coli thioredoxin catalysis, the first requiring a re-orientation of the substrate disulfide bond and the second elongating the substrate disulfide bond. Given this complexity in the catalytic process, it does not seem possible at this stage to propose a reliable molecular interpretation of mutation effects …”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A more recent AFM study achieved sub-angstrom spatial resolution sufficient to detect the rupture of single disulfide bonds in repeated arrays of thioredoxin. 57 …”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%